2020
DOI: 10.1002/fsn3.1443
|View full text |Cite
|
Sign up to set email alerts
|

Gochujang prepared using rice and wheat koji partially alleviates high‐fat diet‐induced obesity in rats

Abstract: The aim of this study was to compare whether gochujang products prepared using giant embryo rice koji (rice gochujang, RG) and wheat koji (wheat gochujang, WG) have anti‐obesity effects on rats fed a high‐fat diet (HFD), who served as a model for obesity. The nutritional composition of RG and WG including proximate constituents, amino acid and fatty acid compositions were investigated. Consequently, the secondary fermented metabolites were analyzed in RG and WG by ultrahigh‐performance liquid chromatography an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Capsaicin has been reported to inhibit lipid accumulation in fat cells and experimental animals as well as reduce white fat pad mass; thus, capsaicin has anti‐obesity effects (Hwang et al., 2005 ). Son et al reported that the fermented food gochujang, which contains many bioactive compounds such as capsaicin and soybean fermentation products, decreases the body weight gain and weights of the liver and white fat pads in HFD‐fed rats (Son et al., 2020 ). Andrea et al showed that capsaicin improves blood lipid levels and reduces hepatic fat accumulation in Western diet‐fed rats (Andrea et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Capsaicin has been reported to inhibit lipid accumulation in fat cells and experimental animals as well as reduce white fat pad mass; thus, capsaicin has anti‐obesity effects (Hwang et al., 2005 ). Son et al reported that the fermented food gochujang, which contains many bioactive compounds such as capsaicin and soybean fermentation products, decreases the body weight gain and weights of the liver and white fat pads in HFD‐fed rats (Son et al., 2020 ). Andrea et al showed that capsaicin improves blood lipid levels and reduces hepatic fat accumulation in Western diet‐fed rats (Andrea et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this result, it can be speculated that daidzein may help ameliorate TG level. This ameliorating effect has been reported to be related to the suppression of hepatic lipogenic-related enzyme activity to a certain extent ( Son et al., 2020 ). However, studies on bull calves and rats showed that daidzein had no obvious effect on serum TG concentration, perhaps due to the animal species, dose and physiological status of the animals.…”
Section: Discussionmentioning
confidence: 88%
“…However, the anti-obesity effects of fermented SLs and fermented IESLs have not been reported till now; this is the first study to compare and evaluate the anti-obesity effects of UFIESLs and FIESLs. Fermented foods, such as mulberry leaves [ 38 ], Gochujang [ 39 ], barley [ 40 ], celery [ 41 ], and fruits [ 42 ], with diverse microorganism strains [ 43 ], typically have stronger anti-obesity effects due to their production of organic acids, free amino acids, phenolic compounds, and isoflavones (daidzein and genistein) during fermentation [ 38 , 39 , 40 , 41 , 42 , 43 ]. Particularly, phenolic compounds in fermented plants are considerably correlated with anti-obesity effects [ 43 ].…”
Section: Resultsmentioning
confidence: 99%